Policing Effects on Black Entrepreneurs’ Financial Performance: The Moderating Impact of Formal and Informal Institutions - Ikenna Uzuegbunam (Administrative Sciences, 2025)
The purpose of this study is to provide a context-based empirical investigation of the racialized effect of policing on the financial performance of Black entrepreneurs. Given the historical role of race in policing in the United States, we expect that the degree of the policing of the Black population in a state will be negatively associated with the financial performance of Black entrepreneurs in the state. The sample for this study is drawn from quarterly police stop data across 14 states from the Stanford Open Policing Project, which is matched with state-level data from the Merchant Maverick ranking of best states for Black entrepreneurs. The sample size is 164 observations over 2013–2015 pertaining to police search rates of Blacks. Findings from the moderated, multivariate regression analysis reveals that the adverse effect of the policing of Black Americans on Black entrepreneurs’ financial performance can be relieved by state-level religiosity and the legalization of marijuana (or cannabis; a mind-altering drug produced from the hemp plant). This research demonstrates the important role of religious and legal institutional mechanisms in countering the economically destructive effects of policing on Black entrepreneurship in the United States.